Application-Based Transportation Technology Analysis: Case Study of PT. Gojek Indonesia - Royani, Solihin; Ruswandi, Ditha Rahayu; Rahmawati, Wulan; Nurkholifah, Annisa; Fauziah, Devi; Maharani, Nabila Sephia Putri (SINTESA, 2025)
Currently, the development of technology and information throughout the world is increasingly rapid. Digital transformation has changed the face of global industry significantly. One striking example is PT. Gojek Indonesia, a technology company from Indonesia, has played an important role in changing the paradigm of transportation services in Southeast Asia. Gojek offers online transportation services that provide solutions to various problems faced by society, and access to this service can be done anytime and anywhere. PT Gojek Indonesia is now known as one of the leading technology companies in the country, with a variety of services including motorbike taxi transportation, goods delivery, and digital payment systems. This article will present an in-depth analysis of Gojek's journey, starting from its initial founding by Nadiem Makarim to its current position as an industry leader. Through a SWOT analysis approach, this article will also explore the strengths, weaknesses, opportunities and threats facing Gojek. Apart from that, the strategies implemented by the company to achieve its goals will also be explained in detail. In this article, we will also highlight Gojek's advantages and disadvantages in meeting customer needs as well as the challenges that must be faced in facing competition with conventional industries and developments in electronic media.